Perancangan Sistem Informasi Penjualan Kopi Robusta di Café 86 Berbasis Web (Studi Kasus: Café 86) - Muhamad Faisal; Maulana Fansyuri (CV. Multi Kreasi Media, 2023)
Cafe 86 is a coffee shop engaged in the beverage sector that sells a wide variety of drink menus by offering a varied menu, with good taste and quality of drinks and can meet customer tastes thereby increasing customer loyalty. Cafe 86 itself is located in the Tangerang city area, precisely on Jl. Bintang Sudimara Pinang Rt.03/04. The problem that is currently happening at Cafe 86 is that menu sales are done manually, cashiers are still doing the manual method by recording customer orders, so errors often occur in recording customer orders and resulting in data related to ordering data that is still very prone to being wrong or missing and requires long time. This resulted in less efficient employee work and slightly hampered customer service. The several research methods used include the following: Literature Study Literature study is the first step that researchers take in this study, Needs Analysis In conducting a sales system analysis, data is needed, as well as supporting tools for conducting a sales system analysis, Based on reports made by the author as explained in the previous chapter, the author draws the conclusion that, The resulting website-based application for ordering café 86 menus can make it easier to order drinks and food. because they have used a computerized system. With this web-based café 86 menu ordering application, employee performance becomes efficient because they no longer use the manual method.